Respostas
respondido por:
0
Olá,
para que a matriz A seja simétrica,
, logo:
(I)
(II)
(III)
(II) -> x+1=1 -> x=0
e para que a matriz A seja anti-simétrica:
, logo:
(IV)
(V)
(VI)
(VI) -> x+1 = - 1 -> x = -2.
Atenciosamente,
para que a matriz A seja simétrica,
, logo:
(I)
(II)
(III)
(II) -> x+1=1 -> x=0
e para que a matriz A seja anti-simétrica:
, logo:
(IV)
(V)
(VI)
(VI) -> x+1 = - 1 -> x = -2.
Atenciosamente,
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás